PENERAPAN METODE PEMBELAJARAN WHOLE BRAIN TEACHING PADA MATERI MAPLE - Irsyadi, Mohamad Khafid; Sari, Ayu Silvi Lisvian (Jurnal Tadris Matematika, 2020)
This research is a Classroom Action Research which aims to describe the application of Whole Brain Teaching learning method to Maple material. The steps of the learning model are as follows: (1) Yes-Class, the lecturer observes the readiness of students in starting the lecture by saying "Class" and if the students are ready to respond by answering "Yes", (2) Micro-Lecture, the lecturer delivers Maple material in Computer course I, (3) Okay-Teach, students repeat the explanations that have been delivered by the lecturer, (4) Scoreboard, the lecturer give an assessment of students responses in repeating lecturers' explanations, (5) Hand and Eyes, the lecturer condition the class when the classroom becomes noisy, and (6) Comprehension Check, lecturer gives exercise. The subjects of this study are students of the second semester, Department of Mathematics Education, Academic year 2018/2019 at STKIP PGRI Blitar. The research instrument was the final cycle test, observation sheet and questionnaire. Based on the results of the end of the cycle test, out of 5 students it was found that 5 students had completed 100% learning with very good criteria. This is in accordance with the success criteria ? 80%. From the overall percentage, the average observation of lecturer activities reached 87.09% with good criteria. Meanwhile the overall average percentage of completeness of observations of student activities is 83.46% with good criteria. Based on the questionnaire responses of students obtained an average percentage of 83% with a good success rate. Thus it can be concluded that the research carried out was successful.